RANCANG BANGUN SISTEM BIOFLOK UNTUK PENINGKATAN BUDIDAYA IKAN LELE: PERSPEKTIF ZOOLOGI DAN EKOLOGI - Artika, Wiwit; Ulhusna, Fitrah Asma; Suhartono, Suhartono; Gagarin, Yuri (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2024)
Catfish (Clarias sp.) aquaculture is a promising sector with high economic potential in Indonesia. However, challenges related to production efficiency and environmental sustainability often hinder its growth. This study investigates the design and implementation of a biofloc system aimed at enhancing catfish (Clarias sp.) aquaculture in Gampong Mata Ie, Montasik, Aceh Besar, Indonesia. The biofloc technology presents a promising solution to the challenges of production efficiency and environmental sustainability in catfish farming by optimizing water quality and maximizing feed utilization through efficient nitrogen cycling. Employing both qualitative and quantitative methodologies, the research involved a comprehensive site survey to assess initial conditions and specific requirements of local catfish farming. The biofloc system design encompassed material selection, pond configuration, and technical parameters such as aeration, water circulation, and organic carbon supplementation. Implementation results demonstrated significant improvements in water quality, with ammonia and nitrite levels maintained within safe limits. Additionally, catfish growth was optimized, evidenced by lower feed conversion ratios, indicating enhanced feed efficiency. From a zoological perspective, the biofloc system provides an environment that closely mimics natural conditions, supporting the welfare of catfish. Ecologically, this technology mitigates negative environmental impacts by minimizing waste and water usage. The application of biofloc technology in Gampong Mata Ie underscores its potential to not only enhance production outcomes but also contribute to local economic and environmental sustainability. This research concludes that the biofloc system design and implementation represent an effective and sustainable strategy for catfish farming, offering significant benefits from both zoological and ecological perspectives. It is anticipated that these findings will serve as a reference for catfish farming developers in similar regions and promote the broader adoption of biofloc technology in the Indonesian aquaculture industry.